The characteristics of arterial spin labeling cerebral blood flow in patients with subjective cognitive decline: The Chinese imaging, biomarkers, and lifestyle study - Li, Wenyi; Jiang, Jiwei; Zou, Xinying; Zhang, Yuan; Sun, Mengfan; Jia, Ziyan; Li, Wei; Xu, Jun (Frontiers in Neuroscience, 2022)
Objective We aimed to characterize the potential risk factors and cerebral perfusion of patients with subjective cognitive decline (SCD). Methods This prospective study enrolled consecutive patients from the Chinese Imaging, Biomarkers, and Lifestyle (CIBL) Cohort of Alzheimer’s disease between February 2021 and March 2022. Patients who met the SCD diagnostic criteria were categorized into the SCD group, while those without cognitive complaints or any concerns were assigned to the healthy control (HC) group. The demographic and clinical characteristics and cerebral blood flow (CBF) from pseudo-continuous arterial spin labeling (pCASL) in standard cognitive regions were compared between these two groups. A multivariate analysis was performed to identify independent factors associated with SCD. Results The frequency of family history of dementia in the SCD group was higher compared with the HC group (p = 0.016). The CBF of left hippocampus (p = 0.023), left parahippocampal gyrus (p = 0.004), left precuneus (p = 0.029), left middle temporal gyrus (p = 0.022), right parahippocampal gyrus (p = 0.018), and right precuneus (p = 0.024) in the SCD group were significantly increased than those in the HC group. The multivariate logistic regression analyses demonstrated that the family history of dementia [OR = 4.284 (1.096–16.747), p = 0.036] and the CBF of left parahippocampal gyrus [OR = 1.361 (1.006–1.840), p = 0.045] were independently associated with SCD. Conclusion This study demonstrated that the family history of dementia and the higher CBF within the left parahippocampal gyrus were independent risk factors associated with patients with SCD, which could help in the early identification of the SCD and in intervening during this optimal period.